Mg/Al-chitosan as a Selective Adsorbent in The Removal of Methylene Blue from Aqueous Solutions - Patimah Mega Syah Bahar Nur Siregar; Aldes Lesbani; Risfidian Mohadi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
The use of dyes in the textile industry is detrimental to aquatic biota and humans. Pollution caused by dye waste can be overcome by adsorption methods using adsorbents such as LDH. LDH is known as an adsorbent that is often found in the process of removing dye waste, but repeated use is not effective. This can be overcome by the LDH modification process using a supporting material such as chitosan. Modification of LDH can be done using coprecipitation or precipitation simultaneously at pH 10. XRD analysis where the peaks that appear in Mg/Al-chitosan are similar to the typical peaks of the constituent materials, namely Mg/Al and chitosan. This is confirmed by FTIR analysis where the spectrum that appears in Mg/Al-chitosan is similar to the spectrum in Mg/Al and chitosan. As well as BET analysis where there is an increase in the surface area of Mg/Al after being modified to Mg/Al-chitosan from 5.845 m2/g to 24.556 m2/g. In this study, the selectivity process for the dye mixture was carried out first with the most selective dye for the Mg/Al-chitosan adsorbent was methylene blue. Methylene blue was continued for adsorption processes such as isotherm adsorption kinetics and adsorption thermodynamics as well as adsorbent regeneration studies. The results showed that at 90 minutes the adsorption reached equilibrium. The adsorption capacity of Mg/Al increased after modification using chitosan from 84.746 mg/g to 108.696 mg/g. The adsorption process follows the Langmuir isotherm type where adsorption occurs chemically (monolayer). Regeneration studies show that Mg/Al-chitosan is an adsorbent that can be used repeatedly with stable adsorption effectiveness until the fifth cycle.